Pemanfaatan Metode Pewarnaan Ekstrak Buah Naga (Hylocereus Polyrhizus) Pada Praktikum Identifikasi Total Bakteri Dalam Menumbuhkan Sikap Ilmiah - Nurhayati, Tati; Redjeki, Sri; Widhorini, Widhorini (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2023)
Positive attitude is very important to accelerate student capability to achieve the purpose of learning in learning activity. One way to increase scientific attitude of the student is by doing practical activity. Bacteria identification is one way to support it. The usage of dragon fruit (Hylocereus polyrhizus) to stain the bacteria has done as an alternative. The aim of the study is to determine the usage of dragon fruit (Hylocereus polyrhizus) extract staining method in practical of bacteria identification to increase scientific attitude. This is a quantitative descriptive study. Population include student of biology teacher candidates of Tadris IPA Biology department of IAIN Syekh Nurjati Cirebon. Random samlping was done using one class that consist of 28 student. Scientific attitude scale instrument was used to collect data in forms of observation paper and questionnaires. Te results showed that the overall practical process wass very good with average point of 95.06 and was overall able to increase scientific attitude based on objectivity indicator. Observation result shows the value of 79.46% and 86.16% based on questinaires. These indicated a very good result. Dragon fruit (Hylocereus polyrhizus) extract can be used as staining alternative to identify bacteria forms in kefir milk, yoghurt and pasteurized milk.